آل أبوغوش شيوخ ناحية بني مالك في سنجق القدس في العهد العثماني : ( 1750 - 1860 م / 1163 - 1279 هـ ) - صافي، خالد محمد عطية (جامعة الأقصى, 2014)
تهدف هذه الدراسة إلى تسليط الضوء على آل أبي غوش كزعامة محلية في ناحية بني مالك إحدى نواحي سنجق القدس في العهد العثماني. حيث تم تناول أصل العائلة وبداية نفوذها. ثم ناقشت الدراسة بلورة زعامة العائلة كزعامة محلية في النصف الثاني من القرن الثامن عشر الميلادي، وكيف ازداد نفوذ العائلة في القرن التاسع عشر بحيث أصبحت من الزعامات المحلية التي يشار لها بالبنان، وكيفية علاقاتها مع القوى المحلية الأخرى، والسلطة العثمانية. كما تعرض الدراسة نفوذ العائلة خلال الحكم المصري (1831-1840م)، وكيفية تفاعلها مع الحكم الجديد من حيث المعارضة والتحالف. كما تناقش الدراسة نفوذ عائلة أبو غوش بعد الحكم المصري، ومحاولة استرداد النفوذ والسطوة من خلال الصراع مع الزعامات المحلية الأخرى، ورد السلطات العثمانية. وتعرض الدراسة أيضا انتهاء نفوذ آل أبو غوش كزعامة محلية في النصف الثاني من القرن التاسع عشر. This study aims to shed light on the family of Abu-Gush as a local leadership in the nahiya of Bani-Malk which was one of the nawahy the sunjuq of Jerusalem in the Ottoman period. It tackles the origin of the family and its rise to power. The study discusses the crystallization of its local leadership in the second half of the eighteenth century. It explains the increasing of its power in the first half of the nineteenth century, its relation with the other local leaders, and the Ottoman authority. The study focuses also on the power of the family during the Egyptian rule (1831-1840), and its interaction with the new regime throughout alliances and oppositions. The study deals hegemony of the family after the end of the Egyptian rule, its attempt to recover its influence through the skirmishes with the local leaders, and the reaction of the Ottoman authority. Finally, the study explains the end of its authority in the second half of the nineteenth century.
Keywords: الدولة العثمانية -- القدس -- التاريخ الإسلامي